PENGARUH DEBT TO EQUITY RATIO, RETURN ON EQUITY, EARNING PER SHARE DAN DIVIDEND PAYOUT RATIO TERHADAP PRICE EARNING RATIO (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017) - Cecep Ridwan; Astrid Dita Meirina Hakim; Aris Wahyu Kuncoro (Universitas Budi Luhur, 2019)
Stocks are an alternative for investors to invest in a company, so stock analysis needs to be done by investors. One stock analysis used by investors is fundamental analysis. Fundamental analysis is an assessment of the company's financial data reports. Based on this, the authors conducted research with the aim to determine the effect of Debt to Equity Ratio, Return on Equity, Earning per Share and Dividend Payout Ratio to Price Earning Ratio. The population in this study is a chemical sub-sector manufacturing company listed on the Indonesia Stock Exchange for the period 2013-2017 with a sample of 8 companies selected by the purposive sampling method. This study uses secondary data and panel data regression analysis techniques which then the data is processed using the program Econometric Views 9 and Microsoft Excel 2010. The results of this study indicate that there is a significant influence between Earning per Share and Dividend Payout Ratio to Price Earning Ratio, while Debt to Equity Ratio and Return on Equity have no effect on Price Earning Ratio.